2018
DOI: 10.1371/journal.pone.0203185
|View full text |Cite
|
Sign up to set email alerts
|

A challenge for healthcare but just another opportunity for illegitimate online sellers: Dubious market of shortage oncology drugs

Abstract: IntroductionDrug shortages mean a challenge to healthcare systems. Exposed patients or health care providers may seek alternative resources for these products online. The purpose of our study was to analyze the online availability of oncology shortage drugs at national and at international levels in 2014 and 2016.MethodsWe tested the online accessibility of oncology shortage drugs by simulating the Internet search method of patients. Search results were evaluated according to operational, distributional, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Drug shortages also lead to online purchasing from illegitimate vendors that are difficult to differentiate for the consumers. In addition, such purchasing increased the financial burden for patients as they are available at increased prices than in pharmacies (Jackson et al, 2012;Fittler et al, 2018;Koenraadt and van De Ven, 2018).…”
Section: Economic Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug shortages also lead to online purchasing from illegitimate vendors that are difficult to differentiate for the consumers. In addition, such purchasing increased the financial burden for patients as they are available at increased prices than in pharmacies (Jackson et al, 2012;Fittler et al, 2018;Koenraadt and van De Ven, 2018).…”
Section: Economic Impactsmentioning
confidence: 99%
“…The available online medicines may have quality problems. Many research studies found that online purchasing occurs in high-income countries like Malta, the United Kingdom, Netherlands, with an increased risk of counterfeit medicines and increased drug prices than local purchasing (Jackson et al, 2012;Fittler et al, 2018;Koenraadt and van De Ven, 2018).…”
Section: Clinical Impactsmentioning
confidence: 99%
“…Meanwhile, it evolved into a vehicle for counterfeit vendors since the online space ideally conceals the identity of illegitimate sellers and easily confuses consumers [5]. Although rather contradictory, potential "additional benefits" can be perceived by individuals regarding the illegal online pharmacy market: direct purchasing of prescription-only medicines (POM) without consultation, accessibility of limited or no availability products (controlled drugs, unapproved generics, recalled medications or those with off-label recommendations), discrete payment options using cryptocurrency and lastly, no maximum purchase quantity [3,4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The bolstered distribution of counterfeit medicines and pharmaceutical products can be attributed to the increased use of online pharmacies in recent years [ 8 ] and the ongoing COVID‐19 pandemic scenario. Approximately 40 000 online pharmacies are currently active worldwide, with an increase of 600 every month.…”
Section: Introductionmentioning
confidence: 99%